Polarization properties of the decameter spikes - Shevchuk, Mykola; Melnik, Valentin; Brazhenko, Anatolii; Dorovskyy, Vladimir; Frantsuzenko, Anatolii; Poedts, Stefaan; Magdalenic, Jasmina (Frontiers in Astronomy and Space Sciences, 2024)
An analysis of the observational polarization properties of the decameter spikes is presented in the paper. It is shown that decameter spikes possess high degree of circular polarization with average value of about 60%. In the frames of "leading spot" theory we associated the spikes activity with a certain active region on the solar disk and determined the mode of the emission. Supposing plasma emission mechanism we link and determine coronal plasma and fast electron beam parameters.